2010
DOI: 10.1007/s11270-010-0682-8
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Nitrogen Uptake from Wet Deposition and the Relation with Leaf Wettability and Water Storage Capacity

Abstract: This study assessed the foliar uptake of 15 N-labelled nitrogen (N) originating from wet deposition along with leaf surface conditions, measured by wettability and water storage capacity. Foliar 15 N uptake was measured on saplings of silver birch, European beech, pedunculate oak and Scots pine and the effect of nitrogen form (NH 4 + or NO 3 − ), NH 4 + to NO 3 − ratio and leaf phenology on this N uptake was assessed. Next to this, leaf wettability and water storage capacity were determined for each tree speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 68 publications
2
41
3
1
Order By: Relevance
“…The tendency to higher recovery by older needles found in the present study is contrary to the majority of results found in the literature (Adriaenssens et al 2011;Bowden et al 1989;Boyce et al 1996;Dail et al 2009;Eilers et al 1992). Wilson and Tiley's (1998) study is the only one where recovery was higher or equal in older needles.…”
Section: Naturalcontrasting
confidence: 99%
See 3 more Smart Citations
“…The tendency to higher recovery by older needles found in the present study is contrary to the majority of results found in the literature (Adriaenssens et al 2011;Bowden et al 1989;Boyce et al 1996;Dail et al 2009;Eilers et al 1992). Wilson and Tiley's (1998) study is the only one where recovery was higher or equal in older needles.…”
Section: Naturalcontrasting
confidence: 99%
“…Redistribution pattern of this N is still unknown. Senescent and dead needles and branches also have the capacity to retain some N even if they are non-active (Adriaenssens et al 2011). The treated trees will be destructively sampled at the end of the experiment, which will allow a thorough assessment of the 15 N repartition.…”
Section: Soilsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower NO 3 − and NH 4 + concentrations and fluxes observed under canopy compared to bulk precipitation, including in the dormant season, show that these two forms of inorganic N were absorbed by foliage, also in the senescent stage, and by branches. Adriaenssens et al (2011) likewise found a significant uptake of nitrogen, mostly of NH 4 + but also of NO 3 − , by the senescent leaves of European beech. Nitrogen uptake at leaf senescence was assumed by these authors to be linked to N retranslocation by trees (see also Houle et al 1999).…”
Section: General Effect Of the Tree Canopy On Precipitation Chemistrymentioning
confidence: 72%